2019
DOI: 10.1016/j.jshs.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent sprint and plyometric training on endurance running performance

Abstract: PurposeThe purpose of this study was to compare the effects of intermittent sprint training and plyometric training on endurance running performance.MethodsFourteen moderately trained male endurance runners were allocated into either the intermittent sprint training group (n = 7) or the plyometric training group (n = 7). The preliminary tests required subjects to perform a treadmill graded exercise test, a countermovement jump test for peak power measurement, and a 10-km time trial. Training included 12 sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…22 In addition, possessing higher muscular strength would also mean that the rate of muscular fatigue would be lower for any given power output as the intensity of the muscle contraction to produce that power output would be relatively lower, hence allowing individuals to better sustain a given running speed which would lead to shorter time to complete the race. 5 Moreover, ground contact time decrease as running speed increase. 21 Endurance runners hence need to possess greater rate of force development in the lower limb to generate sufficient amount of force within the shorter ground contact period in order to run faster.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 In addition, possessing higher muscular strength would also mean that the rate of muscular fatigue would be lower for any given power output as the intensity of the muscle contraction to produce that power output would be relatively lower, hence allowing individuals to better sustain a given running speed which would lead to shorter time to complete the race. 5 Moreover, ground contact time decrease as running speed increase. 21 Endurance runners hence need to possess greater rate of force development in the lower limb to generate sufficient amount of force within the shorter ground contact period in order to run faster.…”
Section: Discussionmentioning
confidence: 99%
“…16 Kinematic data for calculation of the stiffness characteristics were obtained by placing an optical system consisting of 2 bars (Optogait, Microgait, Italy) beside the moving belt of the treadmill. 5 Running Economy: The RE was calculated by combining aerobic energy metabolism, calculated from VO2 and the respiratory exchange ratio (RER), with anaerobic energy metabolism, calculated from the change in Bla. 17…”
Section: Leg and Vertical Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Plyometric training is based on the fact that the quicker the muscles are stretched, the more power they exert; it has been reported to enhance significantly the power of various muscles [ 15 ]. Further, plyometric training is an excellent exercise for developing power, and it is the most widely used training worldwide to enhance power [ 16 ]. We designed the program with a focus on plyometric training but also to improve cardiopulmonary endurance, based on the effective characteristics of previous studies on the advantage of plyometric training [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Determinants of performance for this activity include cardiovascular endurance, lactate threshold and movement economy [6]. Multiple studies have shown that participating in isotonic strength and/or plyometric training resulted in improved running performance without increase in maximal oxygen consumption [7,41,48,53]. To our knowledge, there are currently only 2 studies that investigated the effects of IST on running performance [2,18].…”
Section: Running Performancementioning
confidence: 99%